Experiences of growing and eating: school gardens as educational practice, from educators' perspective - Coelho, Denise Eugenia Pereira; Bógus, Cláudia Maria (Saúde e Sociedade, 2016)
Given the contemporary social scene, rebuilding the bond between food and nature is an important perspective for developing educational practices within the area of food and nutrition. This way, school gardens can be an important educational strategy, with possibilities to produce learning by direct contact with food and nature. This study aimed to understand the production of meanings related to food, among educators, due to their involvement with school gardens. It was a qualitative study, based on philosophical hermeneutics. For data collecting, in-depth interviews were conducted with teachers, staff, and the heads of three public schools in the city of Embu das Artes, São Paulo, Brazil. The development of the school gardens allowed participants to experience meanings related to: horizontal learning and exchange of experiences; practical learning; building of health care, through subjective and intersubjective experiences; strengthening of bonds with nature, with people and with food. School gardens are an important pedagogical proposal which opens many possibilities to think the relationship with food.